Konglomerat travme - Kuhar, Metka (Teorija in praksa, 2020)
In Slovenia, the first study on adverse childhood experiences (ACEs) was conducted in 2019 with a large panel sample of adults. In this paper, the prevalence, interrelatedness and socio-demographic backgrounds of ACEs are presented. More than three-quarters of the participants had experienced at least one ACE while over one-quarter had four or more ACEs. The most frequently reported ACEs were emotional abuse and physical abuse. Consistent with previous studies, the results show that different ACEs often co-occur and are more common in families with a low socioeconomic status. Earlier studies reveal the significant impact of ACEs on people's physical, mental and social functioning throughout their lives, underlying the important need to address ACEs with a comprehensive national strategy and implementation plans in the relevant sectors.
Keywords: addiction; child neglect; Childhood; childhood adversity; Demografski podatki; Demographic data; duševno zdravje; mental health; nasilje; obremenjujoče izkušnje iz otroštva OIO; Otroštvo; Post-traumatic stress disorder; Posttravmatska stresna motnja; poverty; revščina; trauma; travma; violence; zanemarjanje otrok; zasvojenost